Production of zinc nanoparticles using Aspergillus Niger - Ariffin, Ainnur Farhana; Ibrahim Ali , Noorbatcha; Mohd. Salleh, Hamzah (2014)

(untitled)
A simple method for the production of zinc nanoparticles is described. Zinc nanoparticles were produced using Aspergillus niger and zinc sulfate. One at a time optimization method (OFAT) was used to determine microbe's biomass, salt concentration and temperature that will affect the zinc nanoparticles production. The zinc nanoparticles were partially charac- terized visually as well as using SEM and TEM.